Punto de partida : apuntes para una coleccion : guia didactica - 5 caminos hacia el arte actual. - Abramović, Marina; Bonito Oliva, Achille; Bourgeois, Louise; Gallardo, Bosco; Kosuth, Joseph; Reinhardt, Ad (Sevilla : CAAC (Centro Andaluz de Arte Contemporaneo), 2000)
Salinas, Manuel ; Equipo 57 ; Espaliu, José ; Gordillo, Luis ; Peinado, Francisco ; Pérez Villalta, Guillermo ; Campo, Salomé del ; Perez Siquier, Carlos ; Mendieta, Ana ; Pérez, Marta Maria ; Romero, Pedro G. ; Moraza, Juan Luis ; Kosuth, Joseph
Spaans
boek